Variation of Small Scale Magnetic Fields Over a Century using Ca-K Images as Proxy. (1st April 2023) - Singh, Jagdev; Priyal, Muthu; Ravindra, B.; Bertello, Luca; Pevtsov, Alexei
Abstract: A combined uniform and long-time series of Ca-K images from the Kodaikanal Observatory, Mount Wilson Observatory and Mauna Loa Solar Observatory was used to identify and study the Ca-K small-scale features and their solar cycle variations over a century. The small scale features are classified into three distinct categories: enhanced network, active network and quiet network. All these features show that their areas vary according to the 11 yr solar cycle. The relative amplitude of the Ca-K network variations agrees with that of the sunspot cycle. The total area of these small-scale features varies from about 5% during the minimum phase of the solar cycle to about 20% during its maximum phase.